USM SCHOOL OF DENTAL SCIENCES FOUNDING DEAN MAKES HIS MARK AT UAE - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 14 February 2016 – Portraying the eversmiling face and also being of humble character, the founding dean of Universiti Sains Malaysia (USM) School of Dental Sciences (PPSG), Professor Dato' Dr. Ab. Rani Samsudin, 57, now holds the post of Director of the Dental Hospital at the University of Sharjah, United Arab Emirates (UAE).